Measurement of the Z gamma -> nu(nu)over-bar gamma production cross section in pp collisions at root s=8 TeV and limits on anomalous ZZ gamma and Z gamma gamma trilinear gauge boson couplings - (:unkn) unknown (ELSEVIER, 2016)
An inclusive measurement of the Z gamma -> nu(nu) over bar gamma production cross section in pp collisions at root s = 8 TeV is presented, using data corresponding to an integrated luminosity of 19.6fb(-1) collected with the CMS detector at the LHC. This measurement is based on the observation of events with large missing energy and with a single photon with transverse momentum above 145 GeV and absolute pseudorapidity in the range vertical bar eta vertical bar < 1.44. The measured Z gamma -> nu<(nu)over bar>gamma production cross section, 52.7 +/- 2.1(stat) +/- 6.4(syst) +/- 1.4(lumi) fb, agrees well with the standard model prediction of 50.0(-2.2)(+2.4) fb. A study of the photon transverse momentum spectrum yields the most stringent limits to date on the anomalous ZZ gamma and Z gamma gamma trilinear gauge boson couplings. (C) 2016 The Author(s). Published by Elsevier B.V.
Keywords: Photon; MET; SECTOR